2021
DOI: 10.2147/ijn.s316767
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of 68/67Ga-Radiolabeled Sphingolipid Nanoemulsions by PET and SPECT Imaging

Abstract: Background and Purpose Non-invasive imaging methodologies, especially nuclear imaging techniques, have undergone an extraordinary development over the last years. Interest in the development of innovative tracers has prompted the emergence of new nanomaterials with a focus on nuclear imaging and therapeutical applications. Among others, organic nanoparticles are of the highest interest due to their translational potential related to their biocompatibility and biodegradability. Our group has develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…56,57 Previous results from our group highlight the potential of SNs for the development of new cancer therapeutics. [34][35][36][37][38] For gene therapy applications, they have already been tested for delivery of microRNA (miRNA) and pDNA upon modification with the cationic lipids DOTAP and stearylamine. 14,58 Here, we have selected putrescine, a natural polyamine presented in eukaryotic cells for which cancer cells are ravenous due to their increased metabolic activity, 26,59 as the cationic material for the development of a new type of cationic SNs 14,33,34 for cancer gene therapy applications.…”
Section: Development Of Cationic Putrescine Nanosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…56,57 Previous results from our group highlight the potential of SNs for the development of new cancer therapeutics. [34][35][36][37][38] For gene therapy applications, they have already been tested for delivery of microRNA (miRNA) and pDNA upon modification with the cationic lipids DOTAP and stearylamine. 14,58 Here, we have selected putrescine, a natural polyamine presented in eukaryotic cells for which cancer cells are ravenous due to their increased metabolic activity, 26,59 as the cationic material for the development of a new type of cationic SNs 14,33,34 for cancer gene therapy applications.…”
Section: Development Of Cationic Putrescine Nanosystemsmentioning
confidence: 99%
“…In this work, we propose the incorporation of a putrescine derivative, oleamide-modified putrescine, in sphingomyelin nanosystems (SNs), previously developed by our group, 14,[33][34][35][36][37][38][39] and composed by vitamin E, a GRAS-listed excipient, 40 and sphingomyelin, one of the main components of cell membranes. 41 We aim to prove the therapeutic potential of putrescine-SNs (PSNs) that associate a plasmid encoding the apoptotic Fas Ligand (FasL) 42,43 for treating highly aggressive triple-negative breast cancer (TNBC).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that plain SNs composed by a VitE:SM (1:0.1) mass ratio present high potential for targeted drug delivery, gene therapy, and molecular imaging applications. [ 4,32–36 ] In addition, a narrow distribution together a size below 100 nm and a negative zeta potential were reported for the SNs (1:0.1) formulations. [ 6 ] Therefore, we have selected for the thermodynamic study this basic formulation to evaluate how surface modifications can influence the interaction with BSA.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, their significant versatility has been proven, being able to associate with a wide variety of molecules in cancer diagnosis and therapy. 24–26…”
Section: Introductionmentioning
confidence: 99%